2020
DOI: 10.3390/cells9071569
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Replication Site of Tula Orthohantavirus Resides within a Remodelled Golgi Network

Abstract: The family Hantaviridae within the Bunyavirales order comprises tri-segmented negative sense RNA viruses, many of which are rodent-borne emerging pathogens associated with fatal human disease. In contrast, hantavirus infection of corresponding rodent hosts results in inapparent or latent infections, which can be recapitulated in cultured cells that become persistently infected. In this study, we used Tula virus (TULV) to investigate the location of hantavirus replication during early, peak and persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Additional open questions relate to the exact cellular localization of viral genome replication and transcription as well as their regulation. Several studies present contradictory results regarding the replication and transcription site with the involvement of stress granules, P bodies, and different subcellular locations [ 86 , 89 , 100 ]. Importantly, most of the current studies used the overexpression of the N protein [ 71 , 86 , 100 ], which likely results in artificial distributions of the protein and the induction of cellular stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional open questions relate to the exact cellular localization of viral genome replication and transcription as well as their regulation. Several studies present contradictory results regarding the replication and transcription site with the involvement of stress granules, P bodies, and different subcellular locations [ 86 , 89 , 100 ]. Importantly, most of the current studies used the overexpression of the N protein [ 71 , 86 , 100 ], which likely results in artificial distributions of the protein and the induction of cellular stress.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, RVFV N protein localization partially overlaps with P body-resident proteins [ 88 ]. In contrast, a recent study found no significant colocalization of TULV N protein and P body markers but reported significant colocalization of TULV RNA and N protein with stress granule-resident T-cell restricted intracellular antigen 1 (TIA-1) as well as an increase in the number of stress granules in TULV-infected cells [ 89 ]. Stress granules, similar to P bodies, are non-membranous compartments but rather serve as storage sites for translation-stalled mRNAs under cellular stress more than as sites of RNA decay.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations